2014
DOI: 10.1186/1471-2474-15-321
|View full text |Cite
|
Sign up to set email alerts
|

Can pain influence the proprioception and the motor behavior in subjects with mild and moderate knee osteoarthritis?

Abstract: BackgroundOsteoarthritis (OA) is a chronic disease, usually characterized by pain, which is associated with reduced muscle strength, disability and progressive loss of function. However, the pain influence over proprioception and motor behaviour remains unclear. Thus, the purpose of the study was to identify the levels of pain, the proprioceptive acuity and the pattern of muscle recruitment during stair ascent and descent in elderly patients with mild and moderate osteoarthritis (OA) compared to healthy subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…This increased activation may have reflected a pattern aimed at balancing muscle forces across a damaged joint (Astephen Wilson et al 2011 ). As well, pain did not affect either proprioceptive acuity or thigh muscle EMG amplitudes during a stair climbing task in people with mild to moderate knee OA (de Oliveira et al 2014 ). Thus, it remains unclear whether the presence of pain increases or decreases in muscle amplitudes of the quadriceps and hamstrings in people with knee OA.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This increased activation may have reflected a pattern aimed at balancing muscle forces across a damaged joint (Astephen Wilson et al 2011 ). As well, pain did not affect either proprioceptive acuity or thigh muscle EMG amplitudes during a stair climbing task in people with mild to moderate knee OA (de Oliveira et al 2014 ). Thus, it remains unclear whether the presence of pain increases or decreases in muscle amplitudes of the quadriceps and hamstrings in people with knee OA.…”
Section: Discussionmentioning
confidence: 96%
“…However, the opposite has also been observed, where data from 40 participants with mild to moderate knee OA showed that pain was related to greater electromyography (EMG) amplitude and duration in knee OA (Astephen Wilson et al 2011 ). Finally, a recent study discovered that pain did not influence thigh muscle EMG amplitudes or proprioceptive acuity in people with mild and moderate knee OA (n = 31) during a stair climbing task (de Oliveira et al 2014 ). These disparate findings show that the relationships of pain and muscle activation during strengthening exercise remain unclear in knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…9 It is physically demanding, requires greater functional ability than level walking, places greater demands on lower limb joint ROM, 10 and is easily influenced by the knee pain. 11 In comparison with stair ascent, stair descent exhibits faster gait velocity 9 and knee angular velocity 12 in patients with KOA. Moreover, patients with KOA experience smaller maximum knee and hip flexion angles during stair descent than their non-symptomatic counterparts.…”
mentioning
confidence: 99%
“…2 As limitações funcionais na OAJ incluem restrições para caminhar, subir e descer escadas, 3 e qualquer outra atividade que exija descarga de peso sobre o membro afetado. 4 Como o caso do agachamento unipodal, o qual tem sido avaliado, e se mostrou eficiente em revelar diferenças cinemáticas e cinéticas.…”
Section: Introductionunclassified